FACTORS CONTRIBUTING TO POOR HR PERFORMANCE IN FISCAL ADMINISTRATION - Gabriel Ioan AVRĂMESCU (Management & Marketing, 2020)
The purpose of an employee performance management system within the tax administration is to optimize individual achievements and individual excellence in achieving the strategic objectives, objectives, and subobjectives of ANAF. One of the objectives of an employee performance management system is to create a solid foundation for performance management by establishing a culture of performance and learning within the National Tax Administration Agency, as well as by ensuring that all employees know and understand what is expected from them. In this paper we researched the factors that determine poor performance within ANAF, research conducted among managers.